PENDUGAAN PRODUKTIVITAS CABAI RAWIT DI KABUPATEN MAGELANG DENGAN MEREDUKSI FREKUENSI AMATAN PANEN MELALUI PENDEKATAN SIMULASI - Purnama, Yohanes (Informatika Pertanian, 2019)
Abstract One of the strategic policies for developing horticulture in Indonesia is the development of a horticulture management information system. The main concern of the policy is to obtain accurate data in a short period through improving methods of collecting and processing data, increasing data and information, and synchronizing horticultural statistics. The method used to collecting chili data was measuring production in each harvest. This was very draining time, energy and funds that are not small. In addition, another obstacle faced is the location of sample plots that are quite difficult to reach. Based on these conditions, there was a need to simplify the technique of data collection by reducing the frequency of harvest observations. The data used in this study were primary and simulation data. Primary data is the result of a survey of cayenne pepper production by the General Director of Horticulture on several sample plots in Magelang District, Central Java Province in 2018. Simulation data were obtained by generating productivity values based on parameters from primary data. The variable generated was the productivity of each farmer per harvest.. Estimation of productivity involves several factors such as sample sizes (15, 45 and 90), frequency of harvest observations (1, 2 or 3 times) and sampling methods (simple random sampling and stratified random sampling). Evaluation of the estimation results is measured by the variety and bias values. The results of the analysis show that the estimation of productivity using two points with stratified random sampling method and sample size of 90 farmers produce the smallest variety and bias. The best harvesting point were two points in the middle of the harvest.